2004
DOI: 10.1007/s00198-004-1796-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Klemetti index and heel DXA BMD measurements in the diagnosis of reduced skeletal bone mineral density in the elderly

Abstract: Osteopenia/osteoporosis affect many elderly people and might not be detected until symptoms of fractures occur. Early detection of osteopenia/osteoporosis is important and would allow preventive measures and treatment. Access to screening for osteopenia/osteoporosis is often limited, whereas panoramic radiography is commonly used in dentistry. The aim of this study was to determine the validity of the Klemetti index (KI), measured on panoramic radiographs, in the diagnosis of osteopenia/osteoporosis as defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 28 publications
3
70
0
7
Order By: Relevance
“…Studies have shown that MCI can be used as an indicator of low mandibular BMD, fracture risk and bone remodeling (2,13,16). Researches with different populations assessed their diagnostic capability in relation to DEXA values as reference in the diagnosis of osteoporosis, obtaining satisfactory sensitivity and specificity degrees (17,18). Thus, although based on visual qualitative analysis, the MCI can be used to identify mandibular cortical alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MCI can be used as an indicator of low mandibular BMD, fracture risk and bone remodeling (2,13,16). Researches with different populations assessed their diagnostic capability in relation to DEXA values as reference in the diagnosis of osteoporosis, obtaining satisfactory sensitivity and specificity degrees (17,18). Thus, although based on visual qualitative analysis, the MCI can be used to identify mandibular cortical alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Neki autori (11,12) smatraju da vrijednosti MCI-a omogućuju prepoznavanje razlike između žene s osteoporozom i bez te bolesti. MCI se temelji na Klemettijevoj klasifikaciji promjena u donjem korteksu mandibule izmjerenih na ortopantomografskoj slici (13).…”
Section: Methodsunclassified
“…Some authors (11,12) consider that MCI enables to distinguish between normal and osteoporotic women. The MCI is based on Klemetti's classification of changes in inferior cortex of the mandible which can be observed on panoramic x-ray images.…”
Section: Ajanović I Surmentioning
confidence: 99%
“…Do mesmo modo, as densidades minerais ósseas apresentaram maiores valores em pacientes classificadas como C1. Pacientes classificadas como C1 eram predominantemente normais ou osteopê-nicas, enquanto as pacientes C3 eram osteopênicas ou possuíam diagnóstico densitométrico de osteoporose (50)(51)(52)(53) . A espessura da cortical mandibular abaixo do forame mentual também apresenta correlação com a densidade mineral óssea da coluna lombar e do fêmur proximal (15,47,54) .…”
unclassified
“…Em estudo com 211 pacientes, Halling et al (50) demonstraram correlação entre o índice mandibular cortical e a densidade mineral óssea do calcâneo. Os pacientes com erosão acentuada na cortical possuíam densidade mineral óssea de calcâneo significativamente menor do que o grupo sem erosão ou com erosão moderada.…”
unclassified